Phenolic resin foam and method for producing the same
By combining specific compounds and controlling density, independent bubble rate and compression strength, the low compression strength and high cost problems existing in the construction and fixing process of existing phenolic resin foams are solved, and the effect of efficient and environmentally friendly thermal insulation material is achieved .
Patent Information
- Application Number
- CN201680009535.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-03-24
- Filing Date
- 2016-03-23
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2036-03-23
AI Technical Summary
When using chlorinated or non-chlorinated hydrofluoroolefins, the existing phenolic resin foams have problems such as low compressive strength and independent bubble rate, poor construction processing ability and high fixation cost.
Excellent phenolic resins are prepared by using specific combinations of compounds, including selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons, and controlled density, independent bubble rate and 10% compression strength within a specific range, and a specific range of phenolic resins are prepared by controlling the density, independent bubble rate and 10% compression strength within a specific range. Foam body.
It realizes phenolic resin foam with small environmental load, high compression strength, excellent construction handling properties and low fixed costs, meeting the needs of thermal insulation materials for residential purposes.
Smart Images

Figure BDA0001374275330000291 
Figure BDA0001374275330000311 
Figure BDA0001374275330000411
Abstract
Description
Technical Field
[0001] The invention relates to a phenolic resin foam and a method for producing the same. Background Art
[0002] In recent years, due to the increase in awareness of energy conservation and the mandatory implementation of the next generation of energy conservation standards, there is a demand for improved airtightness and thermal insulation performance in homes. It is expected that the thickness of the required thermal insulation material will increase with the demand for improved airtightness and thermal insulation performance in homes, but due to the compression of indoor living spaces and the limited space in the wall, there is a problem that the design needs to be changed as the thickness of the thermal insulation material increases.
[0003] Here, as thermal insulation materials for residential use, fiber-based thermal insulation materials headed by glass wool and rock wool, and foamed plastic-based thermal insulation materials formed by foaming styrene resin, urethane resin, and phenolic resin are known. Among them, phenolic resin foam is an excellent thermal insulation material for residential use with low air permeability and thermal insulation performance that is not easily changed over a long period of time. In addition, it is known that the thermal insulation performance of phenolic resin foam is significantly affected by the type and state of the compound contained in the air bubble.
[0004] And, in the past, as the above-mentioned compound used in the phenolic resin foam, chlorofluorocarbon (CFC) with low thermal conductivity was used. But, CFC obviously causes the destruction of the ozone layer and climate change, and therefore abolishes its use based on the Montreal Protocol adopted in 1987. As a result, as the above-mentioned compound, hydrofluorocarbon (HFC) with low ozone depletion coefficient is used instead. But, it still has higher global warming coefficient, therefore, it is expected that CFC, HFC have low thermal conductivity, low ozone depletion coefficient and low global warming coefficient.
[0005] Patent Documents 1, 2, 3, and 4 disclose chlorinated or non-chlorinated hydrofluoroolefins as compounds having low ozone depletion potential, low global warming potential, and flame retardancy.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application No. 2010-522819
[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-064139
[0010] Patent Document 3: Japanese Patent Application Publication No. 2011-504538
[0011] Patent Document 4: Japanese Patent Application Publication No. 2007-070507 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] Patent Document 1, Patent Document 2, Patent Document 3, and Patent Document 4 disclose a variety of chlorinated or non-chlorinated hydrofluoroolefins, among which 1-chloro-3,3,3-trifluoropropene, 1,3,3,3-tetrafluoro-1-propene, 2,3,3,3-tetrafluoro-1-propene, and 1,1,1,4,4,4-hexafluoro-2-butene are recorded as having low ozone depletion coefficients and global warming coefficients, and can be used for foamed plastic insulation materials. However, although these compounds have low ozone depletion coefficients and global warming coefficients, they have high polarity. Therefore, when used in phenolic resin foams, there is a problem of plasticizing the phenolic resin having hydroxyl groups as hydrophilic groups, resulting in reduced compression strength and independent bubble rate. Therefore, when the technology of phenolic resin foams using hydrocarbons is simply replaced with the above-mentioned chlorinated or non-chlorinated hydrofluoroolefins, sometimes a coarse foam with low compression strength and independent bubble rate is formed. On the other hand, in the prior art, the density of the phenolic resin foam needs to be increased in order to improve the compressive strength, which sometimes causes the following problems: the weight becomes larger, the handling property during construction becomes worse, and the cost increases due to the use of other parts or bodies to fix the phenolic resin foam.
[0014] Therefore, an object of the present invention is to provide a phenolic resin foam having a low environmental load (low ozone depletion potential and low global warming potential), high compressive strength, and excellent handling properties during construction and cost savings during fixing, and a method for producing the same.
[0015] Solutions for solving problems
[0016] The present inventors have repeatedly conducted intensive studies to achieve the above-mentioned purpose, and as a result, have found that by using specific compounds and adjusting the density, closed cell ratio and 10% compressive strength to specific ranges, a phenolic resin foam having a small load on the environment, high compressive strength, excellent handling properties during construction and low cost during fixing can be obtained, thereby completing the present invention.
[0017] That is, the present invention provides a phenolic resin foam, characterized in that it contains at least one selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons, and has a density of 20 kg / m 3 Above and 100kg / m 3 Hereinafter, the closed cell ratio is 80% or more and 99% or less, and the 10% compression strength and the density satisfy the relationship of the following formula.
[0018] C≥0.5X-7
[0019] (Where C represents 10% compressive strength (N / cm 2 ), X represents density (kg / m3 ))
[0020] It is preferred that the above-mentioned halogenated hydrocarbons and at least one selected from the group consisting of the above-mentioned chlorinated hydrofluoroolefins and the above-mentioned non-chlorinated hydrofluoroolefins are contained.
[0021] The at least one selected from the group consisting of the chlorinated hydrofluoroolefins and the non-chlorinated hydrofluoroolefins is preferably at least one selected from the group consisting of 1-chloro-3,3,3-trifluoropropene, 2-chloro-3,3,3-trifluoropropene, 1,3,3,3-tetrafluoro-1-propene, 2,3,3,3-tetrafluoro-1-propene and 1,1,1,4,4,4-hexafluoro-2-butene.
[0022] The above-mentioned halogenated hydrocarbon is preferably isopropyl chloride.
[0023] It is preferred that a hydrocarbon having 6 or less carbon atoms is further contained.
[0024] The content of the at least one selected from chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons is preferably 30% by mass or more based on the total amount of the chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins, halogenated hydrocarbons and hydrocarbons having 6 or less carbon atoms.
[0025] Preferably, a nitrogen-containing compound is also contained.
[0026] The nitrogen-containing compound is preferably a compound selected from the group consisting of urea, melamine, quinuclidine, pyridine, hexamethylenetetramine, and a mixture thereof.
[0027] The absolute value of the dimensional change of the phenolic resin foam after three repetitions of the dry-wet cycle is preferably 2.0 mm or less.
[0028] The brittleness of the phenolic resin foam determined in accordance with JIS A 9511 (2003) 5.1.4 is preferably 50% or less.
[0029] Furthermore, the present invention provides a phenolic resin foam laminate, characterized in that a surface material is provided on a first surface and a second surface of the phenolic resin foam, and both of the surface materials have air permeability.
[0030] Furthermore, the present invention provides a method for producing a phenolic resin foam, characterized in that a foamable phenolic resin composition containing a phenolic resin, a surfactant, a curing catalyst, and at least one selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins, and halogenated hydrocarbons is foamed and cured on a surface material, the weight average molecular weight Mw of the phenolic resin determined by gel permeation chromatography is 400 to 3000, the viscosity of the phenolic resin at 40° C. is 1000 to 100000 mPa·s, the viscosity increase rate constant of the phenolic resin is 0.05 (1 / min) to 0.5 (1 / min), and the density of the phenolic resin foam is 20 kg / m 3 Above and 100kg / m 3 Hereinafter, the closed cell ratio of the phenolic resin foam is 80% or more and 99% or less, and the 10% compressive strength of the phenolic resin foam and the density of the phenolic resin foam satisfy the relationship of the following formula.
[0031] C≥0.5X-7
[0032] (Where C represents 10% compressive strength (N / cm 2 ), X represents density (kg / m 3 ))
[0033] Preferably, the phenolic resin has a loss tangent tan δ of 0.5 or more and 40.0 or less at 40° C., and a loss tangent tan δ of 2.0 or more and 90.0 or less at 60° C.
[0034] Effects of the Invention
[0035] The phenolic resin foam of the present invention has the above-mentioned structure, and therefore has a small load on the environment, has a high compressive strength, and is excellent in handling properties during construction and cost savings during fixing.
[0036] Furthermore, according to the method for producing a phenolic resin foam of the present invention, the phenolic resin foam of the present invention having the above-mentioned structure can be easily produced. DETAILED DESCRIPTION
[0037] Hereinafter, this specific embodiment (hereinafter referred to as "this embodiment") will be described in detail. It should be noted that the present invention is not limited to the following embodiment.
[0038] The phenolic resin foam of the present embodiment contains at least one selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons, and has a density of 20 kg / m 3 Above and 100kg / m 3Hereinafter, the closed cell ratio is 80% or more and 99% or less, and the 10% compression strength and the density satisfy the relationship of the following formula.
[0039] C≥0.5X-7
[0040] (Where C represents 10% compressive strength (N / cm 2 ), X represents density (kg / m 3 ))
[0041] In addition, in this specification, at least one compound or a mixture selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons may be referred to as "compound α".
[0042] Here, since the compound α included in the phenolic resin foam of the present embodiment has low ozone depletion potential and global warming potential, the phenolic resin foam of the present embodiment has a small load on the environment.
[0043] The chlorinated hydrofluoroolefin or the non-chlorinated hydrofluoroolefin is not particularly limited, but is preferably 1-chloro-3,3,3-trifluoropropene, 2-chloro-3,3,3-trifluoropropene, 1,3,3,3-tetrafluoro-1-propene, 2,3,3,3-tetrafluoro-1-propene, 1,1,1,4,4,4-hexafluoro-2-butene, or the like, from the viewpoint of thermal conductivity and foaming properties.
[0044] In addition, the above-mentioned halogenated hydrocarbons are not particularly limited. From the viewpoints of thermal conductivity, ozone depletion potential, global warming potential, and boiling point, halogenated hydrocarbons containing at least one hydrogen element, halogenated hydrocarbons not containing two or more halogen atoms, or halogenated hydrocarbons not containing fluorine atoms are preferred, and isopropyl chloride is more preferred.
[0045] The compound α may contain one compound selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons, or may contain a plurality of compounds in combination.
[0046] The phenolic resin foam of the present embodiment may further contain hydrocarbons, carbon dioxide, and the like (preferably hydrocarbons).
[0047] As the above-mentioned hydrocarbon, for example, hydrocarbons with a carbon number of 6 or less can be listed. That is, the phenolic resin foam of the present embodiment may further contain hydrocarbons with a carbon number of 6 or less in addition to at least one compound selected from the group consisting of, for example, chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons. As the above-mentioned hydrocarbons with a carbon number of 6 or less, specifically, n-butane, isobutane, cyclobutane, n-pentane, isopentane, cyclopentane, neopentane, n-hexane, isohexane, 2,2-dimethylbutane, 2,3-dimethylbutane, cyclohexane, etc. can be listed. Among them, it is suitable to use pentanes such as n-pentane, isopentane, cyclopentane, and neopentane; or, butanes such as n-butane, isobutane, and cyclobutane. The above-mentioned hydrocarbons can be used alone or in combination of two or more.
[0048] The phenolic resin foam of the present embodiment is not particularly limited, and may include, for example, a single compound formed by one of the above-mentioned compounds α, or may include a plurality of the above-mentioned compounds α, or may include at least one of the above-mentioned compounds α and at least one of the above-mentioned hydrocarbons. Among them, the phenolic resin foam of the present embodiment preferably includes halogenated hydrocarbons and at least one compound selected from the group consisting of chlorinated hydrofluoroolefins and non-chlorinated hydrofluoroolefins. In addition, from the viewpoint of being able to obtain a foam having a small average cell diameter, a high independent bubble rate and a high compression strength, the phenolic resin foam of the present embodiment, for example, preferably includes at least one of the above-mentioned compounds α and at least one of the above-mentioned hydrocarbons (particularly preferably includes one or two of the above-mentioned compounds α as the first component and includes the above-mentioned hydrocarbons (for example, pentanes such as cyclopentane and isopentane) as the second component).
[0049] When the phenolic resin foam of the present embodiment contains the hydrocarbon having a carbon number of 6 or less, the content of the compound α is not particularly limited. From the viewpoint of a small average cell diameter, a high independent bubble rate, and a low thermal conductivity, for example, relative to the total amount (100 mass%) of the compound α and the hydrocarbon having a carbon number of 6 or less, it is preferably 30 mass% or more (for example, 30 mass% or more and 100 mass% or less), more preferably 40 mass% or more and 100 mass% or less, further preferably 50 mass% or more and 100 mass% or less, particularly preferably 60 mass% or more and 100 mass% or less, particularly preferably 70 mass% or more and 100 mass% or less, and most preferably 80 mass% or more and 100 mass% or less.
[0050] In the present embodiment, as a formaldehyde scavenger for reducing the amount of formaldehyde emitted from the phenolic resin foam, a nitrogen-containing compound may be added to the phenolic resin in order to impart flexibility to the phenolic resin foam.
[0051] As the above-mentioned nitrogen-containing compound, for example, a compound selected from the group consisting of urea, melamine, quinuclidine, pyridine, hexamethylenetetramine and a mixture thereof can be used, and urea is suitable for use. As additives other than nitrogen-containing compounds, nitrogen, helium, argon, metal oxides, metal hydroxides, metal carbides, talc, kaolin, silica powder, silica sand, mica, calcium silicate powder, wollastonite, glass powder, glass beads, fly ash, silica ash, graphite, aluminum powder, etc. can be added. As metal oxides, calcium oxide, magnesium oxide, aluminum oxide, zinc oxide, etc. can be used, as metal hydroxides, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, etc. can be used, as metal carbides, calcium carbonate, magnesium carbonate, barium carbonate, zinc carbonate, etc. can be used. In addition, as additives other than nitrogen-containing compounds, silane compounds and siloxane compounds can also be added. They can be used alone or in combination. As the aforementioned silane compounds, hexamethyldisilazane and dimethoxydimethylsilane can be used, and as the aforementioned siloxane compounds, hexamethyldisiloxane can be used. The aforementioned silane compounds and siloxane compounds are non-polar and therefore difficult to mix with polar phenolic resins. Therefore, a large number of bubble nuclei are formed, thereby obtaining a foam having a small bubble diameter and a high independent bubble ratio. The aforementioned nitrogen-containing compounds and additives other than the aforementioned nitrogen-containing compounds may be used alone or in combination of two or more thereof.
[0052] The density of the phenolic resin foam in this embodiment is 20 kg / m 3 Above and 100kg / m 3 Below, preferably 20kg / m 3 Above and 70kg / m 3 Below, more preferably 20kg / m 3 Above and 40kg / m 3 Below, more preferably 22kg / m 3 Above and 35kg / m 3 Below, most preferably 23kg / m 3 Above and 28kg / m 3 If the density is less than 20kg / m 3 , the bubble membrane is thinner, so the bubble membrane is easily damaged during foaming, making it difficult to obtain a highly independent bubble structure, and the compression strength is extremely reduced. In addition, if the density is higher than 100kg / m 3 , the solid thermal conductivity of the solid components, including the resin, increases and the thermal insulation performance decreases.
[0053] It should be noted that the density is a value measured by the method described in "(2) Foam Density" described later (Evaluation). The density can be adjusted by, for example, the ratio of the compound α, the hydrocarbon, the ratio of the curing catalyst, the foaming temperature, the molecular weight of the phenolic resin, the reaction rate, the viscosity of the phenolic resin, etc.
[0054] The inventors of the present invention have found that when the hydrocarbon in the conventional hydrocarbon-containing phenolic resin foam is simply replaced with compound α, the viscosity increase associated with the curing reaction of the phenolic resin in the foaming and curing step of the phenolic resin foam is partially offset by the high compatibility of compound α in the phenolic resin, and the growth rate of the bubbles becomes relatively faster. Therefore, it is found that when only the hydrocarbon is replaced with compound α, it is difficult to obtain a phenolic resin foam with high compression strength, excellent handling properties during construction and cost consumed during fixing. In addition, when repeated in-depth studies were conducted, it was found that the reason is related to the independent cell rate and compression strength becoming too high or too low.
[0055] Furthermore, the present inventors have found that by using a phenolic resin having manufacturing conditions, in particular, Mw, viscosity, viscosity increase rate constant, and tan δ within specific ranges, physical properties such as closed cell ratio and compressive strength can be within specific ranges, and by satisfying the physical property values, a phenolic resin foam having high compressive strength and excellent handling properties during construction and cost savings during fixing can be obtained.
[0056] The closed cell rate of the phenolic resin foam in this embodiment is 80% to 99%, preferably 85% to 99%, more preferably 88% to 99%, and particularly preferably 90% to 99%. If the closed cell rate is too low, hydrocarbons and compound α contained in the bubbles are easily replaced by air, so the thermal insulation performance deteriorates after a long time, the bubble film is easily damaged, and the compression strength is reduced, so it is not preferred.
[0057] It should be noted that the above-mentioned closed cell ratio refers to a value measured by the method described in "(3) Closed cell ratio" described later (Evaluation). The above-mentioned closed cell ratio can be adjusted by, for example, the viscosity of the phenolic resin, the type or ratio of the above-mentioned compound α or the above-mentioned hydrocarbon, the curing conditions, the oven temperature during foaming and curing, etc.
[0058] The 10% compressive strength of the phenolic resin foam in the present embodiment is not particularly limited, but is preferably 6 N / cm, for example, from the viewpoint of not excessively increasing the strength and density of the phenolic resin foam (not excessively increasing the weight and the manufacturing cost). 2 Above and 50N / cm 2 Below, more preferably 8N / cm 2 Above and 50N / cm 2 Below, more preferably 10N / cm2 Above and 40N / cm 2 Below, particularly preferably 12N / cm 2 Above and 40N / cm 2 Below, most preferably 15N / cm 2 Above and 40N / cm 2 the following.
[0059] It should be noted that the 10% compressive strength is a value measured by the method described in "(4) 10% compressive strength" described later (evaluation). The 10% compressive strength can be adjusted by, for example, the molecular weight, viscosity, reaction rate of the phenolic resin, the type or ratio of the compound α or the hydrocarbon, curing conditions (e.g., the amount of curing catalyst added, heating time), foaming conditions (e.g., oven temperature), the structure of the foam (a structure in which the cell membrane has no holes, etc.), etc.
[0060] The phenolic resin foam in the present embodiment has a 10% compressive strength and a density that satisfy the following relationship from the viewpoints of strength against compression, handling properties during construction, and reduction of cost for fixing.
[0061] C≥0.5X-7
[0062] (where C represents the above 10% compressive strength (N / cm 2 ), X represents the above density (kg / m 3 ))
[0063] Among them, from the viewpoint of further excellence in terms of strength relative to compression, handling ease during construction, and reduction in cost consumed during fixing, the left side (C) of the above formula is preferably greater than the right side (0.5X-7) by 0.5 or more, more preferably greater by 0.8 or more, further preferably greater by 1.0 or more, and particularly preferably greater by 1.5 or more.
[0064] In addition, if the above relationship is satisfied and the density is 20 kg / m 3 As described above, the strength of the foam is excellent. For buildings with phenolic resin foam constructed on the ground or flat roof, the phenolic resin foam is unlikely to have surface dents or cracks when people walk on it during construction or maintenance.
[0065] The absolute value of the dimensional change after repeated 3 wet-dry cycles of the phenolic resin foam in the present embodiment (the absolute value of the dimensional change) is preferably below 2.0mm, more preferably below 1.6mm, further preferably below 1.3mm, and most preferably below 1.0mm. If the absolute value of the dimensional change is greater than 2.0mm, then when the phenolic resin foam is applied, the joint of the insulation board formed by the foam opens a gap, causing the thermal insulation performance of the building to be impaired, so it is not preferred. On the other hand, when the phenolic resin foam expands, the joint of the plate can bulge, causing the smoothness of the wall to be impaired and the appearance to deteriorate, so it is not preferred.
[0066] It should be noted that the absolute value of the dimensional change is a value measured by the method described in "(5) Absolute value of dimensional change after three repetitions of dry-wet cycles" described later (Evaluation). The absolute value of the dimensional change can be adjusted by, for example, the molecular weight or reaction rate of the phenolic resin, the type or ratio of the compound α or the hydrocarbon, the amount of curing catalyst added or the curing time of the phenolic resin, the oven temperature during foaming and curing, etc.
[0067] The brittleness of the phenolic resin foam in this embodiment is preferably 50% or less, more preferably 40% or less, further preferably 30% or less, particularly preferably 20% or less, particularly preferably 15% or less, and most preferably 10% or less. If the brittleness is greater than 50%, the production cost becomes high, which is not preferred. Furthermore, when the phenolic resin foam is processed into a board during construction, there is a tendency that the foam is easily damaged, which is not preferred.
[0068] It should be noted that the brittleness is a value measured by the method described in "(6) Brittleness" described later. The brittleness can be adjusted by, for example, the composition and proportion of the phenolic resin, the presence or absence of additives such as nitrogen-containing compounds and plasticizers, the density of the phenolic resin foam, the crosslinking density of the phenolic resin in the phenolic resin foam, etc.
[0069] The phenolic resin foam in the present embodiment can be produced by, for example, foaming and curing a foamable phenolic resin composition comprising a phenolic resin and a compound α (preferably a phenolic resin, a surfactant, a curing catalyst and a compound α). The foamable phenolic resin composition may further contain hydrocarbons, and may also contain additives such as nitrogen-containing compounds, plasticizers, flame retardants, curing aids, silane compounds, and siloxane compounds. In addition, in order to more precisely control the foaming and curing speeds, a plasticizer such as phthalates may also be added.
[0070] The manufacturing method of the phenolic resin foam of the present embodiment can be the following manufacturing method: for example, a foamable phenolic resin composition containing a phenolic resin, a surfactant, a curing catalyst and a compound α is foamed and cured on a surface material, the weight average molecular weight Mw of the above-mentioned phenolic resin determined by gel permeation chromatography is greater than or equal to 400 and less than or equal to 3000, the viscosity of the above-mentioned phenolic resin at 40°C is greater than or equal to 100000 mPa·s and the viscosity increase rate constant of the above-mentioned phenolic resin is greater than or equal to 0.05 (1 / minute) and less than or equal to 0.5 (1 / minute).
[0071] The phenol resin can be obtained, for example, by using a compound having a phenyl group and a compound having an aldehyde group or a derivative thereof as raw materials and polymerizing them by heating in the temperature range of 40° C. to 100° C. using an alkali catalyst.
[0072] As the above-mentioned compound having a phenyl group used for preparing the above-mentioned phenolic resin, for example, phenol, resorcinol, catechol, o-cresol, m-cresol or p-cresol, xylenols, ethylphenols, p-tert-butylphenol, etc. can be listed. Among them, phenol, o-cresol, m-cresol or p-cresol are preferred, and phenol is most preferred. As the compound having a phenyl group, a compound having a dinuclear phenyl group can also be used. These compounds having a phenyl group can be used alone or in combination of two or more.
[0073] When two or more compounds having phenyl groups are used, the "molar amount of the compound having phenyl groups" is the sum of the molar amounts of the various compounds having phenyl groups used. In addition, when a compound having dinuclear phenyl groups is used, the value obtained by multiplying the number of moles of the compound having dinuclear phenyl groups by 2 is used as the molar amount of the compound having dinuclear phenyl groups to calculate the "molar amount of the compound having phenyl groups".
[0074] Examples of the compound having an aldehyde group or its derivative used to prepare the phenolic resin include formaldehyde, p-formaldehyde, 1,3,5-trioxane, tetracarbaldehyde, etc. Among them, formaldehyde and p-formaldehyde are preferred. These compounds having an aldehyde group or their derivatives may be used alone or in combination of two or more.
[0075] When two or more compounds having an aldehyde group or derivatives thereof are used, the "molar amount of the compound having an aldehyde group or derivatives thereof" is the sum of the molar amounts of the various compounds having an aldehyde group or derivatives thereof used. It should be noted that the "molar amount of the compound having an aldehyde group or derivatives thereof" when using paraformaldehyde is calculated using a value obtained by dividing the weight of the paraformaldehyde used by 30, the "molar amount of the compound having an aldehyde group or derivatives thereof" when using 1,3,5-trioxane is calculated using a value obtained by multiplying the number of moles of 1,3,5-trioxane used by 3, and the "molar amount of the compound having an aldehyde group or derivatives thereof" when using tetracarboxaldehyde is calculated using a value obtained by multiplying the number of moles of tetracarboxaldehyde used by 4.
[0076] The molar ratio of the compound with aldehyde group or its derivative relative to the compound with phenyl group (molar amount of the compound with aldehyde group or its derivative / molar amount of the compound with phenyl group) used to prepare the above-mentioned phenolic resin is preferably 1.5 or more and 3 or less, more preferably 1.6 or more and 2.7 or less, further preferably 1.7 or more and 2.5 or less, and most preferably 1.8 or more and 2.2 or less. By making the molar ratio of the compound with aldehyde group or its derivative relative to the compound with phenyl group be 1.5 or more, it is possible to suppress the reduction in the strength of the bubble film during foaming and maintain the strength of the phenolic resin foam. In addition, in order to make the amount of the compound with aldehyde group or its derivative required for cross-linking the phenol cores to each other sufficient, cross-linking can be fully performed, so that the bubble film strength of the phenolic resin foam can be improved and the independent bubble rate can be improved. By making the molar ratio of the compound with aldehyde group or its derivative relative to the compound with phenyl group be 3 or less, it is easy to make the phenolic resin cross-linked, and the bubble film strength of the phenolic resin foam can be improved and the independent bubble rate can be improved.
[0077] The weight average molecular weight Mw of the phenolic resin determined by gel permeation chromatography by the method described in "(7) Weight average molecular weight Mw of phenolic resin" described later (evaluation) is, for example, preferably 400 to 3000, more preferably 500 to 3000, further preferably 700 to 3000, particularly preferably 1000 to 2700, and most preferably 1500 to 2500. By making the weight average molecular weight Mw less than 400, a large number of addition reaction sites remain in the phenol nucleus, so that the heat release after mixing the curing catalyst with the phenolic resin becomes large, and therefore, the phenolic resin plasticized by at least one selected from the group consisting of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons becomes high temperature, and the viscosity is further reduced. As a result, the compression strength is reduced due to the rupture of bubbles induced during foaming and the reduction of the independent bubble rate. In addition, if the weight-average molecular weight Mw is not sufficiently increased, then the phenolic resin is not applied with sufficient stretching when foaming, so there is a tendency that the compressive strength reduces. And then, as mentioned above, when foaming and curing is caused because of the viscosity reduction of phenolic resin, the unification of bubbles is easily occurred, and the hole becomes more, and forms the large coarse and inferior foam of average cell diameter. In addition, if the weight-average molecular weight Mw is greater than 3000, the viscosity of phenolic resin becomes too high, and is therefore difficult to obtain necessary expansion ratio, so it is not preferred. In addition, because the low-molecular weight component in the phenolic resin tails off, the heat generated when the solidification of phenolic resin reduces, and sufficient curing reaction can not be carried out, thereby there is the suspense that the compressive strength reduces.
[0078] The viscosity of the above-mentioned phenolic resin at 40°C is, for example, preferably 1000mPa·s or more and 100000mPa·s or less. In addition, from the viewpoint of increasing the independent bubble rate and reducing the average cell diameter, it is more preferably 5000mPa·s or more and 50000mPa·s or less, and particularly preferably 7000mPa·s or more and 30000mPa·s or less. If the viscosity of the phenolic resin is too low (for example, less than 5000mPa·s), the bubble nuclei in the phenolic resin are unified during foaming and curing, so there is a tendency for the cell diameter to become too large. Furthermore, the bubble film is easily broken by the foaming pressure, so there is a tendency to cause the independent bubble rate to deteriorate. If the viscosity of the phenolic resin is too high (for example, greater than 100000mPa·s), the foaming speed slows down, so the necessary foaming ratio cannot be obtained, so it is not preferred.
[0079] The viscosity at 40°C is a value measured by the method described in (8) "Viscosity of phenolic resin at 40°C" in (Evaluation). The viscosity at 40°C can be adjusted by, for example, adjusting the weight average molecular weight Mw or water content of the phenolic resin, adding a plasticizer, etc.
[0080] The viscosity increase rate constant of the above-mentioned phenolic resin is, for example, preferably 0.05 (1 / minute) or more and 0.5 (1 / minute) or less, more preferably 0.05 (1 / minute) or more and 0.4 (1 / minute) or less, further preferably 0.07 (1 / minute) or more and 0.35 (1 / minute) or less, and most preferably 0.08 (1 / minute) or more and 0.3 (1 / minute) or less. If the viscosity increase rate constant is lower than 0.05 (1 / minute), the curing reaction of the phenolic resin will not be fully carried out during foaming, so the bubbles will rupture and form a coarse foam, resulting in a decrease in compressive strength. Furthermore, since the cross-linking reaction of the phenolic resin will not be fully carried out, the strength of the resin portion in the foam will be reduced, and there is a possibility that sufficient compressive strength will not be exhibited. If the viscosity increase rate constant is greater than 0.5 (1 / min), the heat of reaction associated with curing of the phenolic resin in the early stage of foaming becomes too large, and this heat is accumulated in the foam, causing the foaming pressure to become too high, inducing cell breakage and reducing the compressive strength.
[0081] It should be noted that the above-mentioned viscosity increase rate constant refers to a value measured by the method described in "(9) Viscosity increase rate constant" described later (Evaluation). The above-mentioned viscosity increase rate constant can be adjusted by, for example, the type or ratio of the compound having a phenyl group or the compound having an aldehyde group or their derivatives when synthesizing the phenolic resin, the weight average molecular weight Mw of the phenolic resin, the amount of the nitrogen-containing compound added, the amount of the curing catalyst added, etc.
[0082] The tanδ (loss tangent) of the phenolic resin at 40°C is not particularly limited, but is, for example, preferably 0.5 to 40.0, more preferably 0.5 to 35.0, and even more preferably 0.5 to 30.0 from the viewpoint of closed cell ratio and compressive strength.
[0083] The tanδ (loss tangent) of the phenolic resin at 50°C is not particularly limited, but is, for example, preferably 1.25 to 65.0, more preferably 2.0 to 60.0, and even more preferably 4.0 to 55.0 from the viewpoint of closed cell ratio and compressive strength.
[0084] The tanδ (loss tangent) of the phenolic resin at 60°C is not particularly limited, but is, for example, preferably 2.0 to 90.0, more preferably 2.0 to 80.0, and even more preferably 4.0 to 70.0 from the viewpoint of closed cell ratio and compressive strength.
[0085] The phenolic resin preferably has a loss tangent tanδ of 0.5 or more and 40.0 or less at 40°C, and a loss tangent tanδ of 2.0 or more and 90.0 or less at 60°C. The loss tangent tanδ at 40°C, the loss tangent tanδ at 50°C, and the loss tangent tanδ at 60°C are preferably in the range of (40°C, 0.5), (40°C, 40.0), (60°C, 2 ...) in a graph with temperature as the horizontal axis and loss tangent tanδ as the vertical axis. The loss tangent tanδ in the range of above 40°C and below 60°C is further preferably on the side or inside of a quadrilateral formed by the four points (40°C, 0.5), (40°C, 40.0), (60°C, 2.0), and (60°C, 90.0) (a quadrilateral formed by connecting the coordinates of the four points with a line segment), and the loss tangent tanδ in the range of above 40°C and below 60°C is further preferably on the side or inside of a quadrilateral formed by the four points (40°C, 0.5), (40°C, 40.0), (60°C, 2.0), and (60°C, 90.0) (a quadrilateral formed by connecting the coordinates of the four points with a line segment). That is, the loss tangent tanδ at 40°C, the loss tangent tanδ at 50°C and the loss tangent tanδ at 60°C are more preferably between the straight line y=0.075x-2.5 and the straight line y=2.5x-60 or on each straight line in a graph with temperature as the horizontal axis and the loss tangent tanδ as the vertical axis, and the loss tangent tanδ in the range of 40°C to 60°C is further preferably between the straight line y=0.075x-2.5 and the straight line y=2.5x-60 or on each straight line in a graph with temperature as the horizontal axis and the loss tangent tanδ as the vertical axis.
[0086] As the above four points in the graph with temperature as the horizontal axis and loss tangent tanδ as the vertical axis, more preferred are (40°C, 0.5), (40°C, 35.0), (60°C, 2.0), and (60°C, 80.0), and most preferred are (40°C, 0.5), (40°C, 30.0), (60°C, 4.0), and (60°C, 70.0).
[0087] Even if the viscosity of phenolic resin is the same, its behavior during heating will also change due to the difference of crosslinking state and additives. Tan δ is the ratio of loss elastic modulus to storage modulus, so there is the following tendency: the greater the value, the easier it is for phenolic resin to stretch during foaming, and the smaller the value, the easier it is for phenolic resin to break during foaming. Therefore, if the loss tangent tan δ of phenolic resin is greater than the above-mentioned range, the growth rate of bubble becomes too fast relative to the foaming pressure, thereby causing inducing bubble breaking, and independent bubble rate and compression strength are reduced. In addition, it is difficult to apply stretching to phenolic resin during foaming, so there is also the suspense of not being able to show high compression strength. If the loss tangent tan δ is less than the above-mentioned range, the phenolic resin during foaming is easy to break, so the bubble film and skeleton part of the phenolic resin foam are broken, thereby there is a tendency that the structure becomes discontinuous and the compression strength is reduced.
[0088] In this specification, tan δ (loss tangent) refers to a value measured by the method described in "(10) tan δ" described later (evaluation). The above tan δ can be adjusted by, for example, the type or ratio of the compound having a phenyl group, the compound having an aldehyde group or their derivatives when synthesizing the phenolic resin, the weight average molecular weight Mw of the phenolic resin, the water content in the phenolic resin, additives such as plasticizers, etc.
[0089] Examples of the compound α include the compounds described above.
[0090] The content of the compound α in the foamable phenolic resin composition is not particularly limited. From the viewpoint of thermal conductivity, for example, relative to the total amount (100% by mass) of the phenolic resin and the surfactant, it is preferably 0.5% by mass or more and 25% by mass or less, more preferably 2% by mass or more and 20% by mass or less, further preferably 3% by mass or more and 18% by mass or less, and particularly preferably 3% by mass or more and 15% by mass or less.
[0091] In the present embodiment, the total content of the above-mentioned compound α and / or the above-mentioned hydrocarbon is not particularly limited, for example, relative to the total amount (100% by mass) of the above-mentioned phenolic resin and the above-mentioned surfactant, preferably added in a range of 3.0% by mass and 25.0% by mass or less, more preferably 3.0% by mass and 22.5% by mass or less, further preferably 5.0% by mass and 20.0% by mass or less, particularly preferably 6.0% by mass and 18.0% by mass or less, most preferably 6.0% by mass and 15.0% by mass or less. If the addition amount is less than 3.0% by mass, it is very difficult to obtain the necessary expansion ratio, forming a foam with too high a density, and it is impossible to obtain a good foam, so it is not preferred. If the addition amount exceeds 25.0% by mass, the viscosity of the phenolic resin is reduced due to the plasticizing effect of the compound α, and excessive foaming, bubble rupture of the foam, and reduction of the independent bubble rate due to excessive addition of the above-mentioned surfactant are generated, and the physical properties such as long-term thermal insulation performance and compression strength are reduced, so it is not preferred.
[0092] In this embodiment, in order to improve the reduction of the independent cell rate and compression strength associated with the plasticization of the phenolic resin, it is preferred that an inorganic gas such as nitrogen and argon as a cell nucleating agent is added together with the compound α in a range of 0.05% to 5.0% by mass relative to the total amount of the above-mentioned compound α and / or the above-mentioned hydrocarbon, more preferably 0.05% to 3.0%, further preferably 0.1% to 2.5%, particularly preferably 0.1% to 1.5%, and most preferably 0.3% to 1.0%. If the addition amount is less than 0.05%, the effect as a cell nucleating agent cannot be fully exerted, and if the addition amount exceeds 5.0%, the foaming pressure becomes too high during the foaming and curing process of the phenolic resin foam, so the bubbles of the foam are broken, and a coarse foam with a low independent cell rate and compression strength is formed, which is not preferred.
[0093] Examples of the nitrogen-containing compound include the compounds described above.
[0094] As the nitrogen-containing compound, as generally known, the nitrogen-containing compound may be directly added during the reaction of the phenolic resin or at a point near the end of the reaction, or may be mixed with the phenolic resin after reacting with formaldehyde in advance.
[0095] The content of the nitrogen-containing compound is not particularly limited, but is preferably 1% by mass or more and 15% by mass or less, more preferably 2% by mass or more and 10% by mass or less, and particularly preferably 3% by mass or more and 8% by mass or less, relative to the total amount (100% by mass) of the phenolic resin, from the viewpoint of reducing the compounds having an aldehyde group or their derivatives diffused from the phenolic resin foam and the flexibility of the phenolic resin foam.
[0096] As the above-mentioned plasticizer, for example, phthalates, ethylene glycol and diethylene glycol belonging to diols can be listed, among which phthalates are preferably used. In addition, aliphatic hydrocarbons or alicyclic hydrocarbons, or mixtures thereof can be used. The above-mentioned plasticizers can be used alone or in combination of two or more.
[0097] Examples of the flame retardant include bromine compounds such as tetrabromobisphenol A and decabromodiphenyl ether, which are commonly used as flame retardants; phosphorus or phosphorus compounds such as aromatic phosphates, aromatic condensed phosphates, halogenated phosphates, and red phosphorus; and antimony compounds such as ammonium polyphosphate, antimony trioxide, and antimony pentoxide. The flame retardants may be used alone or in combination of two or more.
[0098] As the above-mentioned surfactant, surfactants commonly used for producing phenolic resin foams can be used, among which nonionic surfactants are effective, and preferably, for example, alkylene oxides as copolymers of ethylene oxide and propylene oxide; condensates of alkylene oxides and castor oil; condensates of alkylene oxides and alkylphenols such as nonylphenol and dodecylphenol; polyoxyethylene alkyl ethers having 14 to 22 carbon atoms in the alkyl ether portion, and further fatty acid esters such as polyoxyethylene fatty acid esters; silicone compounds such as polydimethylsiloxane; polyols, etc. These surfactants can be used alone or in combination of two or more.
[0099] The amount of the surfactant used is not particularly limited, but is preferably in a range of 0.3 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the phenolic resin.
[0100] As the above-mentioned curing catalyst, any acidic curing catalyst that can cure the phenolic resin may be used, for example, an acid anhydride curing catalyst is preferably used. As the above-mentioned acid anhydride curing catalyst, phosphoric anhydride and arylsulfonic anhydride are preferably used. As the above-mentioned arylsulfonic anhydride, toluenesulfonic acid, xylenesulfonic acid, phenolsulfonic acid, substituted phenolsulfonic acid, xylene sulfonic acid, substituted xylene phenolsulfonic acid, dodecylbenzenesulfonic acid, benzenesulfonic acid, naphthalenesulfonic acid, etc. can be listed, and they can be used alone or in combination of two or more. The above-mentioned curing catalyst can be diluted with a solvent such as ethylene glycol and diethylene glycol.
[0101] The amount of the curing catalyst is not particularly limited, and is preferably used in a range of 3 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the phenolic resin. In addition, relative to the total amount (100 parts by mass) of the phenolic resin and the surfactant, it can be 3 parts by mass or more and 30 parts by mass or less.
[0102] Examples of the curing aid include resorcinol, cresol, salicin (o-hydroxymethylphenol), and p-hydroxymethylphenol. The curing aids may be used alone or in combination of two or more.
[0103] The foamable phenolic resin composition is not particularly limited and can be obtained by, for example, mixing the phenolic resin, the surfactant, the compound α, the hydrocarbon, the curing catalyst, the nitrogen-containing compound, the plasticizer, and other materials.
[0104] The phenolic resin foam can be obtained by a continuous production method comprising the following steps: for example, the above-mentioned foamable phenolic resin composition is continuously sprayed on a walking surface material, and the surface of the foamable phenolic resin composition that is opposite to the surface of the contact surface material is covered with other surface materials, and the foamable phenolic resin composition is foamed and heat-cured. In addition, as other embodiments, it can also be obtained by the following intermittent production method: the above-mentioned foamable phenolic resin composition is flowed into a mold frame covered by the surface material inside or coated with a mold release agent, and is foamed and heat-cured. The phenolic resin foam obtained by the aforementioned intermittent production method can also be sliced and used along the thickness direction as required.
[0105] It should be noted that in this specification, a laminated board (a laminated board comprising a surface material and a phenolic resin foam) obtained by laminating a phenolic resin foam on a surface material is sometimes referred to as a phenolic resin foam laminated board. The phenolic resin foam laminated board may have one surface material or two surface materials (surface materials (upper surface material and lower surface material) arranged on the first surface (upper surface) and the second surface (lower surface) of the phenolic resin foam). The above-mentioned surface materials are preferably arranged in a form of contacting the phenolic resin foam.
[0106] The above-mentioned surface material is not particularly limited, and is preferably a surface material with air permeability from the viewpoint of removing the moisture (moisture contained in the phenolic resin, moisture produced in the curing reaction (dehydration condensation reaction) etc.) generated during the foaming and curing of the foamable phenolic resin composition, preventing the bubbles from containing water vapor, the internal pressure from becoming too high and causing the broken bubbles, and further improving the independent bubble rate. As the above-mentioned surface material with air permeability, synthetic fiber non-woven fabrics such as polyester non-woven fabrics (polyethylene terephthalate non-woven fabrics etc.), polyamide non-woven fabrics (nylon non-woven fabrics etc.), glass fiber non-woven fabrics, glass fiber paper, paper, metal film with through holes (laminate enhanced by laminating metal foil with through holes with paper, glass cloth, glass fiber) etc. can be listed. Wherein, from the viewpoint of flame retardancy, surface material adhesion strength, preventing the foamable phenolic resin composition from oozing out, preferably PET fiber non-woven fabrics, glass fiber non-woven fabrics, aluminum with through holes. It should be noted that the metal film with through hole can be manufactured by drilling through hole etc. along the thickness direction.Above-mentioned phenolic resin foam laminated board makes moisture easily disperse from phenolic resin foam in foaming and curing by having air permeable face material, therefore can suppress bubble and broken bubble because of water vapor.From this viewpoint, above-mentioned phenolic resin foam preferably has face material at the 1st face (upper surface) and the 2nd face (lower surface), and 2 face materials are air permeability.
[0107] The air permeability of the above-mentioned surface material refers to the oxygen permeability measured according to ASTM D3985-95 of 4.5 cm 3 / 24h·m 2 The above surface material.
[0108] For example, in order to prevent the surface material from breaking during production, the surface material is preferably flexible. As flexible surface materials, for example, synthetic fiber nonwoven fabrics, synthetic fiber woven fabrics, glass fiber paper, glass fiber woven fabrics, glass fiber nonwoven fabrics, glass fiber mixed paper, paper, metal film (metal film with through holes) or combinations thereof can be listed. In order to impart flame retardancy, the surface material may contain a flame retardant. As the flame retardant, bromine compounds such as tetrabromobisphenol A and decabromodiphenyl ether; phosphorus or phosphorus compounds such as aromatic phosphates, aromatic condensed phosphates, halogenated phosphates, and red phosphorus; antimony compounds such as ammonium polyphosphate, antimony trioxide, and antimony pentoxide; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; carbonates such as calcium carbonate and sodium carbonate. The flame retardant can be mixed into the fibers of the surface material, or added to the binder of the surface material such as acrylic acid, polyvinyl alcohol, vinyl acetate, epoxy, and unsaturated polyester. In addition, the surface material can be surface treated with water repellents such as fluororesin, silicone resin, wax emulsion, paraffin, acrylic resin paraffin wax combination system, and asphalt waterproofing agent. These water repellents and waterproofing agents can be used alone or added with the flame retardant and applied on the surface material.
[0109] The temperature of the foamable phenolic resin composition when spraying the foamable phenolic resin composition on the surface material is, for example, preferably 25°C to 50°C, more preferably 30°C to 45°C. By setting the temperature to 50°C or less, foaming is appropriately generated, and a smooth foamed board can be obtained. By setting the temperature to 25°C or more, curing is appropriately generated, and foaming and curing are generated in a good balance.
[0110] The foamed phenolic resin composition sandwiched between the two surface materials can be foamed between the two surface materials. In order to cure the foamed phenolic resin composition (foam), for example, the following first oven and second oven can be used.
[0111] The first oven uses, for example, an endless steel belt type double conveyor or a slat type double conveyor, and performs foaming and curing in an atmosphere of 60° C. to 110° C. The uncured foam is formed into a plate shape and cured in the oven to obtain a partially cured foam. The first oven may have a uniform temperature throughout the entire region or may have a plurality of temperature regions.
[0112] The second oven preferably generates hot air at 70°C or higher and 120°C or lower, and causes the foam that has been partially cured in the first oven to undergo post-curing. The partially cured foam plates can be overlapped at a certain interval using a spacer or a tray. If the temperature in the second oven is too high, the pressure inside the bubbles of the foam becomes too high, thereby inducing bubble breakage. If the temperature is too low, it may take too much time to promote the reaction of the phenolic resin, so it is more preferably 80°C or higher and 110°C or lower.
[0113] Furthermore, in the first oven and the second oven, the internal temperature of the phenolic resin foam is preferably 60° C. to 105° C., more preferably 70° C. to 100° C., further preferably 75° C. to 95° C., and most preferably 75° C. to 90° C. The internal temperature of the phenolic resin foam can be measured, for example, by placing a thermocouple in the foamable phenolic resin composition in the oven and using a data recording function.
[0114] When using compound α, the high compatibility of compound α in phenolic resin causes phenolic resin to be plasticized, so there is the suspense that the viscosity rise part accompanying the curing reaction of phenolic resin is offset in the step of foaming and curing. As a result, when heating in the same oven as the prior art, there is the worry that the phenolic resin foam cannot obtain sufficient hardness. Therefore, the total residence time in the first oven and the second oven is preferably longer than the situation of using hydrocarbon in the past. As the total residence time in the first oven and the second oven, for example, preferably more than 3 minutes and less than 60 minutes, more preferably more than 5 minutes and less than 45 minutes, particularly preferably more than 5 minutes and less than 30 minutes, most preferably more than 7 minutes and less than 20 minutes. If the residence time in the oven is too short, the phenolic resin foam is taken out from the oven under an uncured state, so it becomes a phenolic resin foam with poor dimensional stability and poor quality. If the retention time in the oven is too long, the phenolic resin foam becomes excessively dry and the moisture content becomes too low. Therefore, after being removed from the oven, the foam absorbs a large amount of moisture in the atmosphere, which may cause the sheet to warp. This is not preferred.
[0115] In addition, the foaming and curing methods of the foamable phenolic resin composition for obtaining the phenolic resin foam of the present embodiment are not limited to the above-mentioned methods.
[0116] The phenolic resin foam of the present invention can be used as, for example, a heat insulating material for housing building materials, industrial applications, or industrial applications.
[0117] As described above, according to the production method of this embodiment, it is possible to provide a phenolic resin foam that has a small environmental load, high compressive strength, and excellent handling properties during construction and cost savings during fixing.
[0118] Example
[0119] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0120] (evaluate)
[0121] The following items were measured and evaluated for the phenolic resins and phenolic resin foams in Examples and Comparative Examples.
[0122] (1) Identification of Compound α and / or Hydrocarbons in Phenolic Resin Foam
[0123] First, using standard gases of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins, and halogenated hydrocarbons, the retention time under the following GC / MS measurement conditions was determined.
[0124] The surface material is peeled off from the phenolic resin foam laminate obtained by the embodiments and comparative examples, and about 10 g of the phenolic resin foam sample and a metal file are placed in a 10L container (product name "Tedlar Bag") and sealed, and 5L of nitrogen is injected. The sample is ground from the top of the Tedlar Bag using a file and finely crushed. Then, the sample is placed in a temperature control machine adjusted to 81°C for 10 minutes while being placed in the Tedlar Bag. 100 μL of the gas generated in the Tedlar Bag is taken and GC / MS analysis is performed using the measurement conditions shown below to identify the types of the above-mentioned compound α and / or the above-mentioned hydrocarbons in the phenolic resin foam.
[0125] The presence of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons is confirmed based on the analysis results of GC / MS. The types of chlorinated hydrofluoroolefins, non-chlorinated hydrofluoroolefins and halogenated hydrocarbons are identified based on the retention time and mass spectrum determined in advance. For the above hydrocarbons, the type is determined based on the retention time and mass spectrum. The detection sensitivity of the generated gas components is measured based on various standard gases, and the composition ratio is calculated based on the detection area area and detection sensitivity of each gas component obtained by GC / MS. The mass ratio of each gas component is calculated based on the composition ratio and molar mass of each gas component identified.
[0126] (GC / MS measurement conditions)
[0127] Gas chromatography: "Agilent 7890" manufactured by Agilent Technologies
[0128] Column: "InertCap 5" manufactured by GL Sciences (inner diameter 0.25 mm, film thickness 5 μm, length 30 m)
[0129] Carrier gas: Helium
[0130] Flow rate: 1.1ml / min
[0131] Inlet temperature: 150℃
[0132] Injection method: split flow method (1:50)
[0133] Sample injection volume: 100 μl
[0134] Column temperature: -60°C for 5 minutes, then increase the temperature to 150°C at 50°C / min and maintain for 2.8 minutes
[0135] Mass spectrometry: "Q1000GC" manufactured by JEOL Ltd.
[0136] Ionization method: Electron ionization method (70eV)
[0137] Scanning range: m / Z = 10 to 500
[0138] Voltage: -1300V
[0139] Ion source temperature: 230°C
[0140] Interface temperature: 150℃
[0141] (2) Foam density
[0142] 20 cm square plates were cut out from the phenolic resin foam laminates obtained in Examples and Comparative Examples, and the surface material was removed to measure the mass and apparent volume of the phenolic resin foam. The density (apparent density) was calculated according to JIS K7222 using the obtained mass and apparent volume.
[0143] (3) Independent bubble rate
[0144] The measurement was performed by the following method with reference to ASTM D 2856-94 (1998) A.
[0145] A cubic test piece of about 25 mm square was cut from the center of the thickness direction of the phenolic resin foam in the phenolic resin foam laminate obtained by the examples and comparative examples. In the case where the thickness is too thin to obtain a test piece with a uniform thickness of 25 mm, the surface of the cut cubic test piece of about 25 mm square was sliced into pieces of about 1 mm each, and the test piece with uniform thickness thus obtained was used. The length of each side was measured using a vernier caliper to measure the apparent volume (V1: cm 3 ), and the mass of the test piece was measured (W: 4 significant figures, g). Next, an air pycnometer (TOKYO SCIENCE. Co., Ltd., trade name "MODEL1000") was used to measure the closed space volume (V2: cm 3 ).
[0146] In addition, the average cell diameter (t: cm) was measured according to the method for measuring the average cell diameter in (3) above, and the surface area (A: cm) of the test piece was measured based on the length of each side of the test piece. 2 ).
[0147] The open volume of the cut bubbles on the surface of the test piece (VA: cm) was calculated from t and A using the formula VA = (A × t) / 1.14. 3 ). In addition, the density of the solid phenolic resin was set to 1.3 g / cm 3 The volume of the solid part constituting the cell wall contained in the test piece is calculated by the formula VS = test piece mass (W) / 1.3 (VS: cm 3 ).
[0148] The closed cell ratio was calculated by the following formula (1).
[0149] Closed cell ratio (%) = [(V2-VS) / (V1-VA-VS)] × 100 (1)
[0150] The foam sample produced under the same production conditions was measured six times, and the average value was taken as a representative value.
[0151] (4) 10% compression strength
[0152] A test piece of 100 mm in length and 100 mm in width was cut from the phenolic resin foam laminate obtained by the examples and comparative examples, and the surface material was removed to obtain a test piece. The obtained test piece was cured until the difference between two weighing values taken at intervals of 24 hours in an atmosphere of a temperature of 23° C. and a relative humidity of 50% reached 0.1% or less. The 10% compressive strength of the cured test piece was determined in accordance with JIS K 7220.
[0153] (5) Absolute value of dimensional change after three repeated dry-wet cycles
[0154] A test piece of 300 mm in length and 300 mm in width was cut from the phenolic resin foam laminate obtained by the examples and comparative examples, and the surface material was removed to obtain a test piece. The obtained test piece was placed in an atmosphere of 23°C and 50% relative humidity for 2 weeks. The horizontal (W) and vertical (L) dimensions of the test piece were then measured to obtain the dimension A at the start of the test. 0W , A 0L . Within 12 hours from the start of the test, place the test piece in an atmosphere of temperature 50°C and relative humidity 95%. From 12 hours to 24 hours after the start of the test, place the test piece in an atmosphere of temperature 50°C and relative humidity 35%. From the start of the test to 24 hours is regarded as one cycle, and the test piece is placed until the end of 3 cycles. The end of 3 cycles is 72 hours from the start of the test. Measure the lateral (W) and longitudinal (L) dimensions of the test piece after the end of 3 cycles, that is, 72 hours from the start of the test, and obtain A 72W , A 72L The absolute value of the dimensional change after three repeated dry-wet cycles is calculated as shown in the following formulas (2) and (3). The absolute value of the dimensional change after three repeated dry-wet cycles refers to the larger absolute value of the dimensional change in the longitudinal direction or the transverse direction. In addition, the longitudinal direction and the transverse direction of the test piece refer to the directions perpendicular to the thickness direction of the product.
[0155] The absolute value of the lateral dimensional change after three repeated dry-wet cycles = |A 72W -A 0W | (2)
[0156] The absolute value of the longitudinal dimensional change after three repeated dry-wet cycles = |A 72L -A 0L | (3)
[0157] (6) Brittleness
[0158] Brittleness is calculated according to JIS A 9511 (2003) 5.1.4 by the following operation. From the phenolic resin foam laminate obtained by the embodiment and the comparative example, the surface material of the surface is peeled off, and 12 test pieces are cut into a 25 ± 1.5 mm cube in a way that one surface includes the surface after the surface material is peeled off, and the quality is measured with an accuracy of ± 1%. The test device is as follows: a door is installed on one side of the box, and it can be sealed in a way that dust does not leak out of the box, and an axis is installed outside the central part of the 197 mm surface of the oak wooden box with an inner diameter of 191 × 197 × 197 mm, and it can be rotated at a speed of 60 ± 2 times per minute. 24 oak dices with a specific gravity of 0.65 and a size of 19 ± 0.8 mm after drying are put into the measuring device together with the test piece and sealed, and then the wooden box is rotated 600 ± 3 times. After the rotation is completed, the contents of the box are carefully transferred to a JIS Z 8801 mesh with a nominal mesh size of 9.5 mm, sieved to remove small pieces, and the test piece remaining on the mesh is taken and the mass is measured. The brittleness is calculated by the following formula.
[0159] Brittleness (%) = 100 × (m0-m1) / m0
[0160] (Here, m0: mass of the test piece before the test (g), m1: mass of the test piece after the test (g))
[0161] (7) Weight average molecular weight Mw of phenolic resin
[0162] The weight average molecular weight Mw of the phenolic resin used in Examples and Comparative Examples was determined by gel permeation chromatography (GPC) under the following conditions based on a calibration curve obtained from standard substances (standard polystyrene, 2-hydroxybenzyl alcohol and phenol) described below.
[0163] Pre-treatment:
[0164] About 10 mg of the phenol resin was dissolved in 1 ml of N,N-dimethylformamide (manufactured by Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography), and the solution was filtered using a 0.2 μm membrane filter, and the obtained solution was used as a measurement solution.
[0165] Determination conditions:
[0166] Measuring device: Shodex System 21 (manufactured by Showa Denko K.K.)
[0167] Column: Shodex asahipak GF-310HQ (7.5mmI.D.×30cm)
[0168] Eluent: 0.1 mass % lithium bromide dissolved in N,N-dimethylformamide (manufactured by Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography) was used.
[0169] Flow rate: 0.6ml / min
[0170] Detector: RI detector
[0171] Column temperature: 40°C
[0172] Standard substances: Standard polystyrene (Shodex standard SL-105, manufactured by Showa Denko K.K.), 2-hydroxybenzyl alcohol (99% product, manufactured by Sigma-Aldrich Co.), phenol (special grade, manufactured by Kanto Chemical Co., Ltd.)
[0173] (8) Viscosity of phenolic resin at 40°C
[0174] 0.5 ml of phenolic resin was measured and placed in a rotational viscometer (R-100 model, manufactured by Toki Sangyo Co., Ltd., with a rotor of 3°×R-14). The rotor speed was set so that the viscosity of the phenolic resin to be measured was within the range of 50 to 80% of the upper limit viscosity of the device. The measurement temperature was set to 40°C, and the viscosity value 3 minutes after the start of the measurement was taken as the measured value.
[0175] (9) Viscosity rise rate constant
[0176] To 10 g of the phenolic resin used in Examples and Comparative Examples, 10% by mass of a curing catalyst of 70% by mass of xylenesulfonic acid and 30% by mass of diethylene glycol was accurately weighed and added, and the mixture was thoroughly mixed at 20° C. for 1 minute.
[0177] 0.5 ml of the mixture of the phenolic resin and the curing catalyst is placed in a rotational viscometer (R-100 model, manufactured by Toki Sangyo Co., Ltd., with a rotor of 3°×R-14), and the viscosity at 40°C is measured at intervals of 30 seconds. The X-axis of the measurement result is set as the time (minutes) from the start of the viscosity measurement, and the Y-axis is set as the logarithm of the viscosity (mPa·s), and a single logarithmic plot is performed. The time within 4 minutes to 10 minutes is regarded as a straight line, and its "slope (1 / (minute)" is calculated. This "slope" is recorded as the "viscosity rise rate constant".
[0178] (10)tanδ
[0179] A 50 mm φ aluminum parallel plate fixture is installed on a viscoelasticity measuring device (trade name "ARES", manufactured by TA Instruments). About 2 ml of phenolic resin is placed on the lower parallel plate of the two parallel plates arranged one above the other. Thereafter, the spacing between the parallel plates is set to 0.5 mm, and the resin overflowing from around the parallel plates is scraped off with a spatula. Next, an oven is set to surround the parallel plates. The temperature is set to 40°C, 50°C, and 60°C, and tanδ is measured at each temperature using the measurement conditions described below. After reaching the set temperature, the value read 5 minutes later is used as the tanδ value.
[0180] During the measurement, the distance between the upper and lower parallel plates was set to 0.5 mm, the deformation was set to 10%, and the frequency was 50 Hz. In addition, regarding the adjustment of the measurement temperature, the oven temperature was adjusted in such a way that the thermocouple set on the back side of the lower parallel plate reached a specific temperature among the thermocouples set in the oven and on the back side of the lower parallel plate.
[0181] The obtained tan δ at 40° C., tan δ at 50° C., and tan δ at 60° C. were plotted on a graph with temperature as the horizontal axis and tan δ as the vertical axis to create a graph.
[0182] <Synthesis of Phenolic Resin A>
[0183] 3500 kg of 52% by mass formaldehyde aqueous solution and 2743 kg of 99% by mass phenol were added to the reactor, stirred by a propeller rotary stirrer, and the internal liquid temperature of the reactor was adjusted to 40°C by a temperature controller. Then, 50% by mass sodium hydroxide aqueous solution was added until the pH of the reaction liquid reached 8.7. It took 1.5 hours to raise the temperature of the reaction liquid to 85°C. Thereafter, when the Ostwald viscosity reached 73 centistokes (=73×10 -6 m 2 / s, measured value at 25°C), and 400 kg of urea was added. Thereafter, the reaction solution was cooled to 30°C, and a 50% by mass aqueous solution of p-toluenesulfonic acid monohydrate was added until the pH reached 6.4. The obtained reaction solution was concentrated by a thin film evaporator until the water content in the phenolic resin reached 7.4% by mass. As a result, the viscosity at 40°C was 22000 mPa·s.
[0184] Phenolic resins B to L were obtained in the same manner as in phenolic resin A except that the amount of 52% by mass formaldehyde aqueous solution, the amount of 99% by mass phenol, the Ostwald viscosity, and the amount of urea added shown in Table 1 were changed, and the moisture content in the phenolic resin was adjusted using a thin film evaporator to adjust the viscosity at 40°C.
[0185] [Table 1]
[0186]
[0187] (Example 1)
[0188] A mixture of a block copolymer of ethylene oxide and propylene oxide and 50% of polyoxyethylene dodecylphenyl ether as surfactants, each containing 50% by mass, was mixed at a ratio of 2.0 parts by mass to 100 parts by mass of phenolic resin A. 11 parts by mass of compound A shown in Table 2 and 14 parts by mass of a mixture of 80% by mass of xylenesulfonic acid and 20% by mass of diethylene glycol as a curing catalyst were added to 100 parts by mass of the phenolic resin mixed with the above-mentioned surfactants, and mixed using a mixing head adjusted to 25° C. to obtain a foamable phenolic resin composition.
[0189] The obtained foamable phenolic resin composition is supplied to a moving surface material (lower material). The foamable phenolic resin composition supplied to the surface material has its surface opposite to the surface in contact with the surface material covered with another surface material (upper material), and is clamped by two surface materials and introduced into a first oven having a slat-type double conveyor belt heated to 85°C. After the foamable phenolic resin composition is cured with a residence time of 15 minutes, it is cured in an oven at 110°C for 2 hours to prepare a phenolic resin foam, thereby obtaining a phenolic resin foam laminated board having a phenolic resin foam laminated on the surface material.
[0190] It should be noted that glass fiber nonwoven fabric (trade name "Dura Glass Type DH70 (basis weight 70 g / m 2 )", manufactured by Johns-Manville Corporation).
[0191] [Table 2]
[0192]
[0193] (Example 2)
[0194] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound B was used instead of the compound A and 9 parts by mass of the compound B was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0195] (Example 3)
[0196] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound C was used instead of the compound A and 8.5 parts by mass of the compound C was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0197] (Example 4)
[0198] Compound D was used instead of Compound A. 14 parts by weight of Compound D was added to 100 parts by weight of the phenolic resin mixed with a surfactant. Polyester nonwoven fabrics (trade name "Spunbond E05030, basis weight 30 g / m2) were used as the upper and lower materials. 2 ”, Asahi Kasei Fibers Co., Ltd.), except for this, the same operation as in Example 1 was carried out to obtain a phenolic resin foam and a phenolic resin foam laminate.
[0199] (Example 5)
[0200] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound E was used instead of the compound A and 6 parts by mass of the compound E was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0201] (Example 6)
[0202] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound F was used instead of Compound A and 8 parts by mass of Compound F was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0203] (Example 7)
[0204] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound G was used instead of the compound A and 11 parts by mass of the compound G was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0205] (Example 8)
[0206] Phenolic resin B was used as the phenolic resin, 11 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and polyester nonwoven fabrics (trade name "Spunbond E05030, basis weight 30 g / m2) were used as the upper and lower materials. 2 ”, Asahi Kasei Fibers Co., Ltd.), except for this, the same operation as in Example 1 was carried out to obtain a phenolic resin foam and a phenolic resin foam laminate.
[0207] (Example 9)
[0208] As the phenolic resin, phenolic resin C was used, and 11 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant. As the upper and lower surfaces, polyester nonwoven fabrics (trade name "Spunbond E05030, basis weight 30 g / m 2 ”, Asahi Kasei Fibers Co., Ltd.), except for this, the same operation as in Example 1 was carried out to obtain a phenolic resin foam and a phenolic resin foam laminate.
[0209] (Example 10)
[0210] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin D was used as the phenolic resin and 12 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0211] (Example 11)
[0212] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin D was used as the phenolic resin, compound F was used instead of compound A, and 6 parts by mass of compound F was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0213] (Example 12)
[0214] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin and 12 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0215] (Example 13)
[0216] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin, compound D was used instead of compound A, and 15 parts by mass of compound D was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0217] (Example 14)
[0218] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin, compound F was used instead of compound A, and 7 parts by mass of compound F was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0219] (Example 15)
[0220] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin, compound G was used instead of compound A, and 12 parts by mass of compound G was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0221] (Example 16)
[0222] As the phenolic resin, phenolic resin F was used, and compound B was used instead of compound A. 9 parts by mass of compound B was added to 100 parts by mass of the phenolic resin mixed with a surfactant. As the upper and lower materials, polyester nonwoven fabrics (trade name "Spunbond E05030, basis weight 30 g / m 2 ”, Asahi Kasei Fibers Co., Ltd.), except for this, the same operation as in Example 1 was carried out to obtain a phenolic resin foam and a phenolic resin foam laminate.
[0223] (Example 17)
[0224] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin G was used as the phenolic resin and 13 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0225] (Example 18)
[0226] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound H was used instead of the compound A and 7 parts by mass of the compound H was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0227] (Example 19)
[0228] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound I was used instead of Compound A and 11 parts by mass of Compound I was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0229] (Example 20)
[0230] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound J was used instead of Compound A and 11 parts by mass of Compound J was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0231] (Example 21)
[0232] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound K was used instead of the compound A and 11 parts by mass of the compound K was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0233] (Example 22)
[0234] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin, compound L was used instead of compound A, and 9 parts by mass of compound L was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0235] (Example 23)
[0236] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin E was used as the phenolic resin, compound M was used instead of compound A, and 9 parts by mass of compound M was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0237] (Example 24)
[0238] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound N was used instead of Compound A and 10 parts by mass of Compound N was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0239] (Example 25)
[0240] Phenolic resin E is used as phenolic resin. 10 parts by mass of compound A is added to 100 parts by mass of phenolic resin mixed with a surfactant. In addition, the same operation as in Example 1 is performed to obtain a foamable phenolic resin composition. The foamable phenolic resin composition is flowed into an aluminum mold frame with an internal dimension of 1000 mm in length, 1000 mm in width and 1000 mm in thickness, which is covered by a surface material on the inside, and is sealed. It is fixed with a clamp in a manner that the surrounding and upper and lower surfaces of the mold frame will not expand due to the foaming pressure. It is introduced into an oven heated to 85°C and cured for 60 minutes. Thereafter, the phenolic resin foam is taken out from the mold frame and heated in an oven at 110°C for 5 hours to obtain a block-shaped phenolic resin foam. The surface material used is the same as in Example 1. The obtained block-shaped phenolic resin foam is sliced with a thickness of 50 mm from the center in the thickness direction to obtain a plate-shaped phenolic resin foam.
[0241] (Example 26)
[0242] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that air-permeable aluminum sheets reinforced with glass fiber in which through holes with a diameter of 0.5 mm were drilled at intervals of 20 mm were used as the upper and lower surfaces.
[0243] (Example 27)
[0244] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that 2 parts by mass of hexamethyldisiloxane was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0245] (Example 28)
[0246] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound G was used instead of the compound A and 2 parts by mass of hexamethyldisiloxane was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0247] (Example 29)
[0248] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound I was used instead of Compound A and 2 parts by mass of hexamethyldisiloxane was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0249] (Example 30)
[0250] A phenolic resin foam and a phenolic resin foam laminate were obtained by the same procedure as in Example 1, except that Compound O was used instead of Compound A, 7 parts by mass of Compound O was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0251] (Example 31)
[0252] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that compound P was used instead of compound A, 7 parts by mass of compound P was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0253] (Example 32)
[0254] A phenolic resin foam and a phenolic resin foam laminate were obtained by the same procedure as in Example 1, except that phenolic resin D was used as the phenolic resin, compound O was used instead of compound A, 7 parts by mass of compound O was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0255] (Example 33)
[0256] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound Q was used instead of the compound A and 7 parts by mass of the compound Q was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0257] (Example 34)
[0258] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1, except that phenolic resin E was used as the phenolic resin, compound R was used instead of compound A, 9 parts by mass of compound R was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0259] (Example 35)
[0260] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin F was used as the phenolic resin, compound S was used instead of compound A, and 10 parts by mass of compound S was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0261] (Example 36)
[0262] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that compound T was used instead of compound A, 6 parts by mass of compound T was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0263] (Example 37)
[0264] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound U was used instead of Compound A and 7 parts by mass of Compound U was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0265] (Example 38)
[0266] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound V was used instead of Compound A, 6 parts by mass of Compound V was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0267] (Example 39)
[0268] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin B was used as the phenolic resin, compound W was used instead of compound A, and 10 parts by mass of compound W was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0269] (Example 40)
[0270] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that Compound X was used instead of Compound A, 11 parts by mass of Compound X was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0271] (Example 41)
[0272] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1, except that phenolic resin F was used as the phenolic resin, compound Y was used instead of compound A, 7 parts by mass of compound Y was added to 100 parts by mass of the phenolic resin mixed with a surfactant, and 1 part by mass of phthalate was added as a plasticizer to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0273] (Example 42)
[0274] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that the compound Z was used instead of the compound A and 10 parts by mass of the compound Z was added to 100 parts by mass of the phenolic resin mixed with the surfactant.
[0275] (Comparative Example 1)
[0276] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin H was used as the phenolic resin and 11 parts by mass of compound A1 was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0277] (Comparative Example 2)
[0278] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin I was used as the phenolic resin and 11 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0279] (Comparative Example 3)
[0280] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin J was used as the phenolic resin and 11 parts by mass of compound A1 was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0281] (Comparative Example 4)
[0282] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin K was used as the phenolic resin and 10 parts by mass of compound A was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0283] (Comparative Example 5)
[0284] A phenolic resin foam and a phenolic resin foam laminate were obtained in the same manner as in Example 1 except that phenolic resin L was used as the phenolic resin, compound B was used instead of compound A, and 9 parts by mass of compound B was added to 100 parts by mass of the phenolic resin mixed with a surfactant.
[0285] Tables 3, 4 and 5 show the resins used in the phenolic resin foams obtained in the above Examples and Comparative Examples, their properties, compounds, and the properties and evaluation results of the obtained phenolic resin foams.
[0286] [Table 3]
[0287]
[0288] [Table 4]
[0289]
[0290] [Table 5]
[0291]
[0292] The phenolic resin foams of Examples 1 to 32 have excellent strength against compression, and the weight of the thermal insulation material does not become too heavy, and the handling is also excellent, and the efficiency during construction is improved. In addition, the number of parts and frames used to fix the phenolic resin foam is small, and the cost during construction is also excellent.
[0293] Furthermore, for buildings with phenolic resin foams constructed on the ground or flat roof, the phenolic resin foams of Examples 1 to 32 will not suffer from surface depressions or cracks when people walk on them during construction or maintenance.
[0294] On the other hand, the phenolic resin foams of Comparative Examples 1 to 5 had low compressive strength relative to density and insufficient strength relative to compression. In particular, the phenolic resin foams of Comparative Examples 1 and 3 to 5 had low closed cell ratios and poor thermal conductivity.
[0295] Industrial Applicability
[0296] The phenolic resin foam of the present embodiment has a small load on the environment, has a high compressive strength, is excellent in handling properties during construction and cost for fixing, and can be suitably used for heat insulating materials for residential use, etc.
Claims
1. A method for producing a phenolic resin foam, characterized in that: A foamable phenolic resin composition containing a phenolic resin, a surfactant, a curing catalyst, and at least one selected from the group consisting of chlorinated hydrofluoroolefins and non-chlorinated hydrofluoroolefins is foamed and cured on a surface material. The weight average molecular weight Mw of the phenolic resin determined by gel permeation chromatography is 400 or more and 3000 or less, The phenolic resin has a viscosity at 40° C. of 1,000 mPa·s or more and 100,000 mPa·s or less, The viscosity increase rate constant of the phenolic resin is greater than or equal to 0.05 and less than or equal to 0.5, and the unit of the viscosity increase rate constant is 1 / minute. The phenolic resin has a loss tangent tanδ of 0.5 or more and 40.0 or less at 40°C, and a loss tangent tanδ of 2.0 or more and 90.0 or less at 60°C, wherein the phenolic resin foam contains at least one selected from the group consisting of chlorinated hydrofluoroolefins and non-chlorinated hydrofluoroolefins, The density of the phenolic resin foam is 20 kg / m 3 Above and 100kg / m 3 the following, The independent cell rate is 85% or more and 99% or less. 10% compression strength is 10N / cm 2 above, The 10% compressive strength and the density satisfy the following relationship: C≥0.5X-7 In the formula, C represents 10% compressive strength, X represents density, and the unit of compressive strength is N / cm 2 The unit of density is kg / m 3 , The viscosity rise rate constant is determined as follows: To 10 g of a phenolic resin, a curing catalyst of 70% by mass of xylenesulfonic acid and 30% by mass of diethylene glycol was accurately weighed and added in an amount of 10% by mass relative to the phenolic resin, and the mixture was thoroughly mixed at 20° C. for 1 minute. 0.5 ml of the mixture of the phenolic resin and the curing catalyst was placed in a rotational viscometer, and the viscosity at 40° C. was measured at intervals of 30 seconds. The X-axis of the measurement result was set to the time in minutes from the start of the viscosity measurement, and the Y-axis was set to the logarithm of the viscosity in mPa·s. Single logarithmic plotting was performed, and the time within 4 minutes to 10 minutes was regarded as a straight line, and its slope was calculated as the viscosity increase rate constant.
Citation Information
Patent Citations
Molding material of foamable resol type phenolic resin and phenolic resin foam
JP2007070507A
Hydrochlorofluoroolefin foaming agent composition
JP2010522819A
Foaming agent and composition containing fluorine-substituted olefin, and foaming method
JP2011504538A
Foaming agent and composition containing fluorine substituted olefin, and method of foaming
JP2013064139A
Expandable resol type phenolic resin molding material and phenolic resin foam
CN101258191B